Analisis Konsep Kemaksuman Nabi Muhammad Dalam Tafsir Ruh Al-Ma'ani dan Ai-Kasyaf - Hidayat, Rahmat Ali; Lubis, Zakaria Husin; Ismail, Azmi (Jurnal Global Ilmiah, 2025)
This research was written to study the approach and understanding of Tafsîr Rûh al-Ma'âni and Tafsîr al-Kasysyâf about the context of the Prophet Muhammad's innocence in the Qur'an. The main object of this research is the verses related to the immorality of the Prophet Muhammad. By comparing the interpretations of these two interpretations, it will provide a more comprehensive understanding of the differences of views between Muktazilah and Sunni, it is hoped that it can contribute to deepening the understanding of the Prophet Muhammad's interpretation in the Qur'an and highlight the difference in interpretation between the schools and strengthen previous research that discusses the Prophet Muhammad's teachings. will be compared to understand the perspective of each character in interpreting verses related to the immorality of the Prophet Muhammad. Tafsîr Rûh al-Ma'âni which represents the Sunni view will be analyzed to see how this madhhab influences in interpreting verses related to the Prophet Muhammad's innocence. Similarly, Tafsîr al-Kasysyâf which is associated with the thought of Muktazilah, will be examined to see how they interpret the same verse. This research produced findings that the two interpreters have similarities and differences in interpreting verses related to the immorality of the Prophet Muhammad, especially in the details of the problem and it was found that there are differences in several aspects such as in the problem of minor sins and mistakes attributed to the Prophet Muhammad. In some aspects, Az-Zamakhsari who believes in Muktazilah produces the same interpretation as the Sunni and several times explicitly establishes the immortality of the Prophet Muhammad from great sins and errors in delivering treatises.